Maltodextrin from Cassava Starch (Manihot Utilissima) and Its Application as Encapsulating Agent of Red Guava Juice Extract (Psidium Guajava) - Krisnitya, Widya; Darmadji, Purnama; Pranoto, Yudi (Universitas Ahmad Dahlan, 2020)
Cassava starch is one of the processed products of cassava, which can be made into maltodextrin. Maltodextrin is often applied to the encapsulation method of instant drink packaging in Indonesia. One of the most favorite fruits in the instant drink industry is red guava. The research objectives are to know the characteristic of maltodextrin made by hydrolysis of cassava starch, and to identify the effects of the amount of maltodextrin added to the characteristic of red guava extract produced. In the research, the hydrolysis time of cassava starch is varied into 60, 90, and 120 minutes. Maltodextrin made will be analyzed, and its characteristics on the encapsulation of red guava extract will be defined. The red guava juice is encapsulated by the variants of maltodextrin concentration as 10%, 15%, 20%, and 25%. Red guava extract powder produced from the selected amount of maltodextrin then be analyzed for its characteristics. The results showed that the highest DE was found in maltodextrin with 120 minutes hydrolysis time. The increased amount of maltodextrin added affects the increase of solubility and vitamin C levels of the produced red guava juice extract. The water content is not affected by the amount of maltodextrin added.